The 1994 Elections: The Maine Vote in National Perspective - Moen, Matthew (Maine Policy Review, 1994)
The 1994 elections at the national and state level resulted in significant changes all across the political landscape.University of Maine political scientist Matthew Moen analyzes the nature of that change and its implications for Maine.